Women’s work in the context of closing civic space - Ossome, Lyn (A Journal on African Women’s Experiences, 2018)
The contemporary closing of civic space and the attendant impact on social justice movements is impacting the world of women’s work in ways that ought to be understood against the backdrop of shifts in labour relations, increasing unemployment, expansion of the informal economic sector, low minimum wages, de-unionisation, the growth and waste of the financial sector, deregulation, and changing regimes in taxation, among other factors. This article highlights the nature of social organising among labouring women, drawing on historical contexts to highlight the complexities that emerge in the contemporary period, which are attached both to the nature of the neoliberal state and civil society. Focusing on the legislative and punitive state, the paper examines contradictions that confound the demand for rights where the state is both guarantor of rights and mediator of capital and draws some preliminary conclusions in this regard. For many labouring women in Africa, the modes of struggle and social organising that have historically defined their world have characteristically emanated from below and in relation to their lived contexts and realities. Such struggles have articulated social and economic questions that also critically articulate political questions of autonomy, freedom and equality. In precolonial African kinship systems, the flexibility of gender in the political and cultural system favoured the presence of women in the highest elite core of society, whether in the status acquired through titles, or in the position of the kinship itself. Power and authority emerged out of the reproductive and productive roles that women played in society, and women’s political power emerged out of those roles articulated to daily struggles for survival (Lebeuf, 1963; Amadiume, 1987; Santoru, 1996; Oyewumi, 1997; Ossome, 2018).
Keywords: Women’s work; Context; Civic space